Analisis Keterhubungan Antara Kepuasan, Kesetiaan, Dan Komunikasi Word Of Mouth Dalam Sektor Jasa - Dion Dewa Barata (Ultima Management : Jurnal Ilmu Manajemen, 2009)
The service sector is the sector that is currently growing but because of its non tangible nature, this sector is very dependent on the quality of services delivered by employees or sales representatives. This research was held by conducting literature study and performed the data collection form questionnaires to the consumer services sector in the Greater Jakarta. The data was processed using the analysis of reliability, validity, and methods of SEM (structural equation model) using 240 respondents. The results showed that the perceived satisfaction affect customer loyalty to the salesperson, the perceived customer satisfaction does not affect customer loyalty to service providers, customer loyalty to the salesperson's affect customer loyalty to service providers, customer loyalty toward the salesperson did not contribute to word of mouth customers and contribute to customer loyalty for word of mouth customers. Keywords: Jasa, Kepuasan, WOM, Loyalitas, Loyalty, satisfaction, service, SEM